ROBOTIC REFRACTIVE SURGERY: INCREASED PRECISION FOR VISION CORRECTION. - Maciel , Renato Anatolio Lima Horta; Ladeira , Larissa Melo; Magalhães , Letícia Ferreira Rezende; Lima, Diego Henrique de Melo; Tuyama, Marina Gontijo (Brazilian Journal of Implantology and Health Sciences, 2024)
Robotic refractive surgery emerges as an innovative approach to correct visual disorders such as myopia, hyperopia and astigmatism, leveraging the precision of robotic technology. This technique aims to improve visual acuity and provide more predictable and consistent results, offering a promising alternative to traditional vision correction methods. Objective: To critically analyze scientific studies published in the last 10 years on robotic refractive surgery, focusing on its effectiveness, safety and comparability with conventional vision correction techniques. Methodology: The systematic review was conducted in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The search for relevant articles was carried out in the PubMed, Scielo and Web of Science databases. The descriptors used were "refractive surgery", "robotic eye surgery", "increased precision", "visual correction" and "ophthalmological technology". The inclusion criteria were studies published in the last 10 years, in English or Portuguese, that evaluated the efficacy and safety of robotic refractive surgery in adult patients. Exclusion criteria were duplicate studies, isolated case reports and studies with pediatric populations. Results: Analysis of the selected studies revealed that robotic refractive surgery demonstrated satisfactory visual results, with high precision in correcting refractive errors. Furthermore, the safety of the procedure was highlighted, with low rates of intra- and postoperative complications. Comparatively, robotic refractive surgery presented advantages in terms of stability of results and faster visual recovery when compared to conventional techniques. Conclusion: Robotic refractive surgery represents a significant evolution in the correction of visual disorders, offering greater precision and safety to patients. The results of this systematic review support the effectiveness and feasibility of this technique as a treatment option for those seeking to improve their visual acuity.